Integr[ity] 8: Re-integrative refugee reception facility - Galabova, Alexandra (My University, 2013)
“So often the world sits idly by, watching ethnic confl icts fl are up, as if these were mere entertainment rather than human beings whose lives are being destroyed. Shouldn’t the existence of even one single refugee be a cause for alarm throughout the world?” -- Urkhan Alakbarov (Rector of the Scientifi c Council of the Academy of Public Administration, Azerbaijan) The conventional representation of refugee life in tented, sprawling camps no longer tells the full migrant story. As the world urbanises, refugees and asylum seekers too are progressively moving into built up areas – including large towns and cities. Today, almost half of the world’s 15.2 million refugees reside in urban areas, with only one-third in camps (UNHCR, 2009). Refugees move to the city in the hope of fi nding a sense of community, safety and economic independence. However, in reality, what many actually fi nd is harassment, physical assault and poverty. (Pavenello, 2010) South Africa is home to more than 413,000 new refugees every year (UNHCR 2010). Indeed, the exact size of the refugee population in Johannesburg is not known and there has been little focus on the growing number of refugees living in urban centres. Despite these high numbers, both quantitative and qualitative information available is partial. Urban refugees are scattered over big cities, often highly mobile and reluctant to come forward for support due to fears that they could be deported or sent to refugee camps.